ANALISIS IMPLEMENTASI KEBIJAKAN AUDIT KEPABEANAN DALAM RANGKA PENINGKATAN KEPATUHAN IMPORTIR DI DIREKTORAT JENDERAL BEA DAN CUKAI RAWAMANGUN TAHUN 2022 - 2023 - Handayani, Alya Rohili; Susanto, Imam (Jurnal Ilmu Administrasi Publik, 2025)
This research aims to analyze the implementation of customs audit policies in order to increase importer compliance at the Directorate General of Customs and Excise in Rawamangun in 2022-2023. The method used is qualitative, with a focus on implementing customs audit policies to increase importers at the directorate general of customs and excise. The research results show that the implementation of the customs audit policy regulated in PMK 118 of 2021 has made a positive contribution to importer compliance, even though there are various obstacles such as limited human resources and regulatory complexity. Efforts to overcome these obstacles include increasing coordination between DJBC and importers, as well as utilizing information technology to streamline the audit process. The conclusion of this research confirms that an effective customs audit policy can create a more transparent and accountable system, as well as increase importer compliance with applicable policies.